EFFECTS OF FOLIAR APPLICATION OF ORGANIC AND GROWTH PROMOTER BIOZYME ON GROWTH OF WOLLY PEACH "RED JUNE" 1- VEGETATIVE GROWTH - & Al-Biaty, Al-Karam (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A Field experiment was conducted using Factorial within Randomized Complete Block Design during 2014 and 2015 on the wolly peach seedlings cv Red June, which grafted on the seeded apricot, at the Dept. of Horticulture – Coll. Of Agric. – Univ. of Baghdad. The objective of this experiment was to study the effect of foliar application on organic fertilizer and growth promoter biozyme on growth of wolly peach. The tveatments were organic Fertilizer (Botryfun) (F) with 0, 3, 4 , 5 ( Ml.ltr -1) and biozyme (G) 0 , 2 , 4 ( Ml.ltr -1). The results revealed that the plants foliared by organic fertilizer F4 produced significantly highest values for all the studied traits. Plant hight iricveased 17.6, 35.5 cm, new branches lenyht 56.0, 14.4 cm. no. of vegetative branches 11.5, 29.2, diameter of main stem increased 0.85, 1.13cm, single leaf area 42.0, 39.8 cm2 , no of leaves 517.3, 771.7, leaves dry matter % , 36.8, 41.6, for two years respectively. The biozyme G2 increased plant height 15.8 and 35.6 cm, new vegetative branches 53.9, 62.8 cm, new vegetative branches 10.1, 31.6, stem diameter 0.78, 1.14 cm, single leaf area 37.3, 41.0 cm2 , no. of leaves 431.9, 825.0, leaves dry matter % 37.2, 41.3, for two years, respectively.